Mitochondrial-Derived Vesicles Protect Cardiomyocytes Against Hypoxic Damage - Li, Binghu; Zhao, Hongliang; Wu, Yue; Zhu, Yu; Zhang, Jie; Yang, Guangming; Yan, Qingguang; Li, Junxia; Li, Tao; Liu, Liangming (Frontiers in Cell and Developmental Biology, 2020)
Myocardial ischemia is a condition with insufficient oxygen supporting the heart tissues, which may result from myocardial infarction or trauma-induced hemorrhagic shock. In order to develop better preventive and therapeutic strategies for myocardial ischemic damage, it is important that we understand the mechanisms underlying this type of injury. Mitochondrial-derived vesicles (MDVs) have been proposed as a novel player in maintaining mitochondrial quality control. This study aimed to investigate the role and possible mechanisms of MDVs in ischemia/hypoxia-induced myocardial apoptosis. H9C2 cardiomyocytes were used for the cellular experiments. A 40% fixed blood volume hemorrhagic shock rat model was used to construct the acute general ischemic models. MDVs were detected using immunofluorescence staining with PDH and TOM20. Exogenous MDVs were reconstituted in vitro from isolated mitochondria under different hypoxic conditions. The results demonstrate that MDV production was negatively correlated with cardiomyocyte apoptosis under hypoxic conditions; exogenous MDVs inhibited hypoxia-induced cardiomyocyte apoptosis; and MDV-mediated protection against hypoxia-induced cardiomyocyte apoptosis was accomplished via Bcl-2 interactions in the mitochondrial pathway. This study provides evidence that MDVs protect cardiomyocytes against hypoxic damage by inhibiting mitochondrial apoptosis. Our study used a novel approach that expands our understanding of MDVs and highlights that MDVs may be part of the endogenous response to hypoxia designed to mitigate damage. Strategies that stimulate cardiomyocytes to produce cargo-specific MDVs, including Bcl-2 containing MDVs, could theoretically be helpful in treating ischemic/hypoxic myocardial injury.